G298(P) Sacral dimples in the newborn – doing less (and saving money) safely. (27th April 2015) - Beh, A; Rowland, A; Reynolds, P; Bennett, C
Abstract : Background: Although spinal dysraphism is often detected antenatally, identifying certain signs postnatally, which might indicate increased possibility of an abnormality is important. Sacral dimples are common, but they are probably over-investigated. We set out to audit 4 years of ultrasound scans to see if investigations and follow up arrangements could be improved. Methods: All paediatric spinal ultrasound scans between Febuary 2009 – August 2013 were checked for origin, indication and result. Any with uncertain or positive scans also had MRI scan results and notes review. Results: There were 56 scans performed, aged 0 days to 22 months. The majority were referred from hospital doctors (75%). Other sources included the orthopaedic clinic (16%) and the patient's GP (9%). Only 3 patients were found to have spinal dysraphism confirmed on US scan then MRI. From the 43 patients referred for investigation for a sacral dimple, none had spinal dysraphism. The three patients with spinal dysraphism all had either a skin tag or a hairy patch as an indication for the further investigation. From these results, and in keeping with available evidence, we have simplified the guideline for further investigation. Clinical indicators used to refer for ultrasound scan – Figure 1 Total Referrals for Clinical Indicators Showing Patients with Dysraphism on MRI – Figure 2 Conclusions: The presence of a simple sacral dimple is a poor marker for spinal dysraphism, and as a result we present a new guideline for use. By reducing over-investigation of babies with sacral dimples, there is scope for potential saving on time, resources, inconvenience to parents and cost.